PHENOLIC COMPOUND FROM THE STEM BARK OF MANGGIS HUTAN (Garcinia bancana Miq.) AND THEIR ANTIOXIDANT ACTIVITY - Muharni Muharni; Supriyatna Supriyatna; Husein H. Bahti; Dachriyanus Dachriyanus (Indonesian Journal of Chemistry, 2009)
A phenolic compoud, (-)-epicatechin, was isolated from  the stem bark of Garcinia bancana. The structure of this compound was determined base on spectroscopic  data such as including UV, IR, 1-D, 2-D NMR, and comparison with the reported data. Biological activity of this compound at free radical scavenging activity by 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) and inhibitory xanthine oxidase(XO) activity showed that (-)- epicathechin active at two methods with IC50 value 8.1 and 8.6 mg/mL respectively.